Extracts of Waste from Poplar Wood Processing Alleviate Experimental Dextran Sulfate-Induced Colitis by Ameliorating Oxidative Stress, Inhibiting the Th1/Th17 Response and Inducing Apoptosis in Inflammatory Lymphocytes - Wenjie Wang; Yiwei Zhang; Jiamin Cao; Jiahui Xu; Linguo Zhao; Xianying Fang (MDPI AG, 2021)
As a fast-growing tree, poplar is widely planted and typically used for wood processing in China. During poplar wood processing, a large amount of poplar sawdust (PS) and poplar leaves (PL) are produced and abandoned. To make full use of poplar resources and clarify the use of poplar as a feed additive, the active ingredients in PS and PL were extracted and isolated, and the anti-inflammatory effects of the extracts on mice with dextran sulfate sodium (DSS)-induced colitis were investigated. In vitro anti-inflammatory experiments showed that the ethyl acetate extract of PS and PL (PSE and PLE, respectively) could significantly inhibit the proliferation of concanavalin A (Con A)-activated lymphocytes. Salicortin, tremulacin and salireposide were identified in both PSE and PLE. Oral administration of PSE and PLE rescued DSS-induced colonic shortening, repaired tissue damage, and decreased the disease activity index (DAI). The antioxidant capacity, including the increased activities of glutathione peroxidase (GSH-Px), total superoxide dismutase (T-SOD and catalase (CAT) and decreased activity of myeloperoxidase (MPO), in the colons of mice with colitis was enhanced through the activation of ERK after treatment with PSE and PLE. The ratio of Th1 to Th17 cells, which can lead to inflammation in the spleen, was significantly decreased by the administration of PSE and PLE, while the phosphorylation of related transcription factors (p65, STAT1, and STAT3) was inhibited. Furthermore, PSE and PLE could induce apoptosis in Con A-activated lymphocytes, which may be associated with the increase in p-TBK1, as the molecular docking results also indicated that salireposide in PSE and PLE could interact with the TBK1 protein. Overall, our study provides a promising feed additive for improving intestinal inflammation in animals and a method for the full utilization of poplar resources.